2013
DOI: 10.1002/dvg.22409
|View full text |Cite
|
Sign up to set email alerts
|

A reciprocal translocation dissects roles of Pax6 alternative promoters and upstream regulatory elements in the development of pancreas, brain, and eye

Abstract: Pax6 encodes a transcription factor with key roles in the development of the pancreas, central nervous system, and eye. Gene expression is orchestrated by several alternative promoters and enhancer elements that are distributed over several hundred kilobases. Here, we describe a reciprocal translocation, called 1Gso, which disrupts the integrity of transcripts arising from the 5'-most promoter, P0, and separates downstream promoters from enhancers active in pancreas and eye. Despite this fact, 1Gso animals exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…PAX6 is a member of the PAX gene family and acts as a key regulator in the development of the eyes, central nervous system and pancreas (15,32,33). Furthermore, it has been demonstrated that PAX6 serves an oncogenic role in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAX6 is a member of the PAX gene family and acts as a key regulator in the development of the eyes, central nervous system and pancreas (15,32,33). Furthermore, it has been demonstrated that PAX6 serves an oncogenic role in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Paired box (PAX) 6, a member of the PAX family, is an important transcription factor associated with the development of the eyes, pancreas and central nervous system (14,15). Furthermore, it has been established that deregulated PAX6 is involved different types of human cancer, including non-small cell lung cancer (16), retinoblastoma (17), glioma (18), colorectal cancer (19), prostate cancer (20) and breast cancer (21).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the mutation occurred as a clean breakage-and-reunion event (Fig. 3A) very similar to those documented in the analysis of other germline translocations (Elso et al, 2008; 2013; Elso, 2004). …”
Section: Resultssupporting
confidence: 81%
“…Slides were baked at 41 ° C overnight and stored at −20 ° C until use. Slides were pretreated and hybridizations were performed as described previously [58]. Sections were mounted using Vectashield Mounting Medium with DAPI.…”
Section: Methodsmentioning
confidence: 99%